Analysis of teachers' problems in the implementation of the independent curriculum in PAI subjects - Hafipudin, Hafipudin; Taufik, Muhammad Ihsan; Fauzan, Muhammad Nizar; Purnama, Sephia Sriya Diwi (ARKA INSTITUTE, 2025)
Many students experience obstacles in learning Islamic Religious Education, coupled with the implementation of the Independent Learning Curriculum which is still relatively new in its implementation. The implementation of the Independent Learning Curriculum certainly requires time for adjustment, so this affects student learning outcomes and the achievement of appropriate learning objectives. This study aims to examine the problems that occur at SMA Daarul Qur'an Bandung related to the implementation of the Independent Learning curriculum in learning Islamic Religious Education subjects. The research method used is a qualitative case study approach with data collection through observation, interviews and document studies. The results of the study show that in the implementation of the Independent Learning Curriculum in schools there are still various problems, especially in the teacher aspect. It can be concluded that the Independent Curriculum in Islamic Religious Education subjects at SMA Darul Quran Bandung shows a number of challenges that need to be overcome. By continuing to evaluate and adjust, it is hoped that schools can overcome the challenges faced and improve the quality of learning for students as a whole.